2019
DOI: 10.1016/j.omtm.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Rescues Age-Related Changes in Muscle-Derived Stem/Progenitor Cells from Progeroid Mice

Abstract: Aging-related loss of adult stem cell function contributes to impaired tissue regeneration. Mice deficient in zinc metalloproteinase STE24 ( Zmpste24 −/− ) exhibit premature age-related musculoskeletal pathologies similar to those observed in children with Hutchinson-Gilford progeria syndrome (HGPS). We have reported that muscle-derived stem/progenitor cells (MDSPCs) isolated from Zmpste24 −/− mice are defective in their proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 82 publications
0
27
0
Order By: Relevance
“…In our study, cell proliferation was tested prior to sheet collection and at day 1 and 14, revealing that A-TSPC sheets have significantly lower cell density and proliferation rate than Y-TSPC sheets. Kawakami et al (2019) communicated that progeroid mice contained higher numbers of apoptotic muscle stem/progenitor cells. Taylor et al (2003) showed that in human colonic crypts, age-related DNA mutations are associated with stem cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, cell proliferation was tested prior to sheet collection and at day 1 and 14, revealing that A-TSPC sheets have significantly lower cell density and proliferation rate than Y-TSPC sheets. Kawakami et al (2019) communicated that progeroid mice contained higher numbers of apoptotic muscle stem/progenitor cells. Taylor et al (2003) showed that in human colonic crypts, age-related DNA mutations are associated with stem cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MDSPCs isolated from prelamin A-expressing progeria mice exhibit increased mTOR signaling. This is accompanied by proliferation and differentiation deficiencies in culture and during tissue regeneration [49]. Inhibition of mTOR with rapamycin improved differentiation along myogenic and chondrogenic lineages and reduced the extent of apoptosis and senescence of MDSPCs.…”
Section: The Progeria Cell and Energymentioning
confidence: 99%
“…( 26 ) STE24 was already identified to process prelamin A to a mature nuclear form. ( 30 ) Mutation of Ste24 leads to premature‐aging disease, lipodystrophy, steatohepatitis, and skeletal abnormalities, ( 30,33,34 ) which are often seen in patients with AIDS under anti‐HIV therapies. For RCE1, our results support its association with Rab13 or Rab18, as levels of the two Rab proteins were reduced in the mouse liver treated with the anti‐HIV drugs.…”
Section: Discussionmentioning
confidence: 99%